Early and selective reduction of NOP56 (Asidan) and RNA processing proteins in the motor neuron of ALS model mice. (September 2013) - Miyazaki, Kazunori; Yamashita, Toru; Morimoto, Nobutoshi; Sato, Kota; Mimoto, Takafumi; Kurata, Tomoko; Ikeda, Yoshio; Abe, Koji
Abstract : Objective: There is increasing evidence to support that altered RNA processing is implicated in the pathogenesis of motor neuron degeneration of amyotrophic lateral sclerosis (ALS). We evaluate the expression of three RNA processing-related proteins in ALS model mice in this study. Methods: We analyzed expression and distribution patterns of three RNA processing-related proteins, nucleolar protein (NOP) 56 (identified as causative gene for spinocerebellar ataxia (SCA) 36, nicknamed Asidan), TDP-43, and fused in sarcoma/translocated in liposarcoma (FUS) in lumbar and cervical cords, hypoglossal nucleus, cerebral motor cortex, and cerebellum of transgenic (Tg) SOD1 G93A ALS model mice throughout the course of motor neuron degeneration. Results: Compared to age-matched wild type (WT) mice, Tg mice showed progressive reduction of NOP56 levels in the large motor neurons of lumbar and cervical cords from the early-symptomatic stage (14 weeks of age) to the end stage of the disease (18 weeks). TDP-43 and FUS protein levels showed a later decrease in the nucleus of large motor neuron at 18 weeks (end stage of the disease). These changes were not observed in the primary motor cortex of the cerebrum as well as molecular and granular layers and Purkinje cells in the cerebellum. Discussion: The present study suggests a progressive loss of these three nuclear proteins and subsequent RNA processing problems including a novel gene relating to ALS (NOP56) under the motor neuron degeneration.